Electrospun Nanomaterials Applications in Food, Environmental Remediation, and Bioengineering - Mallavia, Ricardo; Falco, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The papers collected in this Special Issue entitled "Electrospun Nanomaterials: Applications in Food, Environmental Remediation, and Bioengineering" illustrate the high diversity and potential for implementation of electrospun nanofibers in these fields, including the covering of a wide number of subtopics. Examples of these applications have included bioactive scaffolds, wound healing dressings, compound protective nanoreservoirs and sustained and controlled release systems. An important driver of these applications results from advances in materials science and new nanofiber manufacturing processes. Definitely, such pieces of fundamental research will contribute to the promotion of electrospinning as a focal point in the future development of technological applications at the interface of biological systems, which promise long-term benefits for both health and the environment.